SOCIAL ISSUES OF THE RUSSIAN LABOUR MARKET - A. I. Bikchantayeva; D. K. Bikchantayeva (Russian Journal of Economics and Law)
The article views the reforming of the labour market structure, which, by the authors, should be carried out after considering the whole complex of social problems of the modern Russian society, the most burning of which is the protracted demography crisis. Its overcoming is possible only after reconsidering the "lower budget limitations" in the sphere of human capital reproduction. The authors suggest to pay special attention to the system of payment in the budget economy sector